2005
DOI: 10.1007/s00330-005-2836-4
|View full text |Cite
|
Sign up to set email alerts
|

Resolving small pulmonary nodules: CT features

Abstract: Our aim was to analyse the CT morphology of resolving nodules over time in order seek morphologic features helpful in initial nodule classification. The imaging characteristics of 133 consecutive resolving pulmonary nodules detected in 56 subjects in a screening trial for early lung cancer with low-dose CT were retrospectively reviewed by two readers in consensus. Nodule size ranged from 2 to 28 mm, with a mean diameter of 5.9 mm. The maximum diameter of resolving nodules was < or =5 mm in 71/133 (53%), 6-10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 27 publications
0
26
1
Order By: Relevance
“…Radiographic characteristics that have been proposed as useful to analyze pulmonary nodules include [1][2][3][4]12]:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiographic characteristics that have been proposed as useful to analyze pulmonary nodules include [1][2][3][4]12]:…”
Section: Discussionmentioning
confidence: 99%
“…However, compared to CT imaging, sensitivity and specificity for the detection of lung nodules are low. In addition, small lung nodules are a frequent finding specifically in a risk population for bronchial carcinoma, such as heavy smokers [1,2]. Hence, an improved accuracy to determine a lung nodule's likelihood for malignancy would be desirable, i.e., by a reliable detection of calcifications.…”
Section: Introductionmentioning
confidence: 99%
“…Such nodules are detected in 5 to 66% of individuals who smoke (as our trial participant did) (20)(21)(22)(23)(24)(25)(26). Resolution or reduction in size of these nodules is also well recognized, with nodules of less than or equal to 5 mm being the most likely to resolve (20,27). Possible diagnoses that have been proposed for resolving nodules include focal inflammatory lesions, mucoid impaction in small bronchi, or intermittent enlargement of benign intrapulmonary lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Two other screening studies reported confl icting results about potential predictors of resolv ing (and therefore benign) nodules. 18,19 Other studies have used computer-assisted techniques or novel CT scan parameters to discriminate between malignant and benign nodules, but these have been limited by small size, imprecision, and lack of external validation. 20,21 Consequently, although CT scan morphology often helps to estimate the probability of malignancy, it is rarely conclusive.…”
Section: Suitability For Surgery or Othermentioning
confidence: 99%